Changes in fish skin microbiota along gradients of eutrophication in human-altered rivers. Issue 1 (31st January 2022) - Côte, Jessica; Jacquin, Lisa; Veyssière, Charlotte; Manzi, Sophie; Etienne, Roselyne; Perrault, Annie; Cambon, Marine C; Jean, Séverine; White, Joël
ABSTRACT: The skin microbiota plays a major role in health of organisms but it is still unclear how such bacterial assemblages respond to changes in environmental conditions and anthropogenic perturbations. In this study, we investigated the effects of the eutrophication of freshwater ecosystems on the skin microbiota of fish. We sampled wild gudgeon Gobio occitaniae from 17 river sites along an eutrophication gradient and compared their skin microbiota diversity and composition, using a 16s rRNA gene metabarcoding approach. Results showed a tendency for higher taxonomic and phylogenetic diversity in highly eutrophic sites linked to the presence of suspended organic matters. We also highlighted significant links between eutrophication and skin microbiota taxonomic composition and beta-diversity. In contrast, skin microbiota characteristics did not correlate with host factors such as age or sex, although microbiota beta-diversity did vary significantly according to host parasite load. To conclude, our study highlights the importance of environmental factors, especially eutrophication, on the diversity and composition of skin mucus bacterial communities. Because changes in the skin microbiota may induce potential deleterious consequences on host health and population persistence, our results confirm the importance of accounting for host-microbiota interactions when examining the consequences of anthropogenic activities on aquatic fauna. Abstract : Eutrophication, due to anthropogenic pressures, is related to changes in skin microbiota composition and diversity in a freshwater fish species.